Impacto de geradores conectados via inversores na coordenação da proteção em redes de distribuição de energia elétrica - CORDEIRO, Murillo Augusto de Melo (Universidade Federal do Pará, 2018)
Despite its many benefits, the Distributed Generation (DG) can adversely affect some aspects related to the operation performance of electrical power systems, especially a no so deeply explored point: the interaction between the protection systems and inverter-based power generation units. In this dissertation, the impact of inverter-based DGs units on the fuse-recloser coordination schemes used in distribution networks is thoroughly studied. The simulations were conducted using the software package DIgSILENT Power Factory through several single-phase and three-phase short circuits along the distribution network, considering different fault locations, penetration levels of DGs, operating conditions, and other aspects that impact over the protection miscoordination in an IEEE real test distribution system of 34 busbars. The contribution to the short-circuit current of inverter-based generators is also investigated through simulations on electromagnetic transients models available in the software. The simulation results shows that significant inverter-based DG penetration levels on distribution feeders increase the short-circuit current that passes through the fuse and make it operate faster than the recloser in a fault condition, leading to loss of fuse-recloser coordination in a time frame base. A general discussion of the results is performed, identifying some recommended corrective actions that should be considered in order to maintain the coordination and selectivity between the distribution system protection devices located throughout the network.